2010
DOI: 10.1111/j.1524-4733.2009.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

In or Out? Income Losses in Health State Valuations: A Review

Abstract: Seven empirical studies were identified. Overall, it seems that not explicitly mentioning the inclusion of income will induce a minority of respondents to include these effects and this appears not to influence results. More empirical work is needed, using generic instruments, larger samples, and using the interview method of administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 33 publications
0
36
0
1
Order By: Relevance
“…Queda claro que la discusión sobre los dos enfoques propuestos en la literatura está lejos de ser resuelta 11,[40][41][42] . Contar con dos métodos con hipótesis tan dispares, las cuales obviamente se reflejan en resultados muy distintos, supone un handicap para la puesta en prác-tica de evaluaciones económicas desde la perspectiva social.…”
Section: Líneas De Avanceunclassified
“…Queda claro que la discusión sobre los dos enfoques propuestos en la literatura está lejos de ser resuelta 11,[40][41][42] . Contar con dos métodos con hipótesis tan dispares, las cuales obviamente se reflejan en resultados muy distintos, supone un handicap para la puesta en prác-tica de evaluaciones económicas desde la perspectiva social.…”
Section: Líneas De Avanceunclassified
“…Yet, income loss may be small in countries where paid sick leave schemes exist [10]. Furthermore, a recent review on empirical evidence for the consideration of income loss in direct preference-based measures in the United States and other countries concluded that ''not explicitly mentioning the inclusion of income will induce a minority of respondents to include these effects and this appears not to influence results'' [10]. A very recent large-sample survey in the general population of Japan confirmed this finding.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review found that in the absence of instructions, only a minority of respondents actually consider income loss in health state valuations [1]. The purpose of this editorial is to reexamine the valuation of productivity loss and consider the potential for double-counting in a net health benefit framework.…”
mentioning
confidence: 99%
“…The debate regarding the inclusion of productivity costs (PCs) in cost-utility analyses (CUA) continues [1,2]. The concern is that PCs included in the numerator of an incremental costutility ratio (ICUR) may cause double-counting if the productivity loss is also incorporated in health state valuation.…”
mentioning
confidence: 99%
See 1 more Smart Citation